High performance silicon carbide avalanche‐p‐i‐n ultraviolet photodiode with dual operation models. Issue 17 (2nd August 2016) - Zhang, Mingkun; Wang, Kang L.; Jiang, Hexin; Hong, Rongdun; Wu, Zhengyun
Abstract : Silicon carbide‐based quasi‐separated‐absorption‐multiplication ultraviolet avalanche photodiode (APD) with a small‐area multiplication region and a large‐area absorption region, which comprises of a p + nn − junction encircled by a p + n − junction, is proposed, and its optoelectronic performance is modelled. The modelling results show a 4H‐SiC APD with high performance can be achieved. Moreover, when operated at a low reverse bias (e.g. 5.0 V), the photodiode has almost the same optoelectronic characteristics as the 4H‐SiC p‐i‐n photodiode. It is noted that the device has benefited advantages of both conventional separate absorption and multiplication APD and p‐i‐n photodiode in the wavelength range of ultraviolet detection, which enable the dual operation models of the device.